Optical coherence tomography and visual evoked potentials in evaluation of optic chiasm decompression - Poczos, Pavel; Česák, Tomáš; Jirásková, Naďa; Macháčková, Markéta; Čelakovský, Petr; Adamkov, Jaroslav; Gabalec, Filip; Soukup, Jiří; Kremláček, Jan (Scientific reports, 2022)
Chiasmal compression is a known cause of visual impairment, often leading to surgical decompression of the optic chiasm (OC). A prospective study was held at University Hospital in Hradec Králové to explore sensitivity of optical coherence tomography (OCT) and visual evoked potentials (VEPs) to OC compression and eventual changes after a decompression. 16 patients with OC compression, caused by different sellar pathologies, were included. The main inclusion criterion was the indication for decompressive surgery. Visual acuity (VA), visual field (VF), retinal nerve fibre layer (RNFL) and ganglion cell layer (GCL) thickness, and peak time and amplitude of pattern-reversal (P-VEPs) and motion-onset VEPs (M-VEPs) were measured pre- and postoperatively. The degree of OC compression was determined on preoperative magnetic resonance imaging. For M-VEPs, there was a significant postoperative shortening of the peak time (N160) (p < 0.05). P100 peak time and its amplitude did not change significantly. The M-VEPs N160 amplitude showed a close relationship to the VF improvement. Thinner preoperative RNFL does not present a statistically important limiting factor for better functional outcomes. The morphological status of the sellar region should be taken into consideration when one evaluates the chiasmal syndrome. M-VEPs enable detection of functional changes in the visual pathway better than P-VEPs.